Knowledge, Attitude, and Barriers to Fluoride Application as a Preventive Measure among Oral Health Care Providers - Aqdar A. Akbar; Noura Al-Sumait; Hanan Al-Yahya; Mohammad Y. Sabti; Muawia A. Qudeimat (International Journal of Dentistry)
Objective. To investigate the knowledge, attitude, and possible barriers to fluoride application among oral health-care providers in Kuwait. Methods. A validated self-administered questionnaire was distributed to a random sample of 291 dentists. The questionnaire included four categories: dentists’ characteristics, knowledge of and attitude towards fluoride application, factors influencing decision-making on prescription of fluoride, and the clinician’s perception of own knowledge. Means, group differences, and logistic regression were calculated. Results. 262 completed the questionnaire (response rate of 90%). Half of the participants (49%) reported that water fluoridation is the best method for caries prevention in children. Majority of the participants (80%) acknowledged that topical fluoride prevents dental caries, but only 40% frequently use it in their practices. Fear of overdose was a concern in 57% of the participants. About 31% believed that caries is a multifactorial disease and cannot be prevented. In addition, 32% of the dentists who thought caries is multifactorial and cannot be prevented stated that restorations take precedence over preventive therapy. Conclusion. Despite the participants being in favor of topical fluoride application and believing in its effectiveness, certain barriers were apparent such as knowledge deficiencies, products labelling flaw, and lack of participation in effective continuing educational activities.